A novel fluorescent assay for sucrose transporters - Gora, Peter J (BioMed Central, 2012)
BACKGROUND: We have developed a novel assay based on the ability of type I sucrose uptake transporters (SUTs) to transport the fluorescent coumarin β-glucoside, esculin. Budding yeast (Saccharomyces cerevisiae) is routinely used for the heterologous expression of SUTs and does not take up esculin. RESULTS: When type I sucrose transporters StSUT1 from potato or AtSUC2 from Arabidopsis were expressed in yeast, the cells were able to take up esculin and became brightly fluorescent. We tested a variety of incubation times, esculin concentrations, and buffer pH values and found that for these transporters, a 1 hr incubation at 0.1 to 1 mM esculin at pH 4.0 produced fluorescent cells that were easily distinguished from vector controls. Esculin uptake was assayed by several methods including fluorescence microscopy, spectrofluorometry and fluorescence-activiated cell sorting (FACS). Expression of the type II sucrose transporter OsSUT1 from rice did not result in increased esculin uptake under any conditions tested. Results were reproduced successfully in two distinct yeast strains, SEY6210 (an invertase mutant) and BY4742. CONCLUSIONS: The esculin uptake assay is rapid and sensitive and should be generally useful for preliminary tests of sucrose transporter function by heterologous expression in yeast. This assay is also suitable for selection of yeast showing esculin uptake activity using FACS.